Reviewing in the Different Types of Heavy Materials in the Human Teeth (Bulletin of the International Association for Paleodontology, 2024)
Heavy materials can be detected by recording long-term exposures to human teeth due to their stable nature. Teeth have mechanical properties such as hardness, elasticity, viscoelasticity and fracture behaviour. In this review, the level of cadmium, lead, mercury, arsenic and etc. in human dental tissues was evaluated. In order to quantify these materials in teeth, various analytical techniques were used. The results indicated detectable levels of these heavy materials which varied between individuals and locations. Furthermore, there was a correlation between dietary habits, tooth type, age, gender, occupational exposures, and dental heavy material concentrations. Health implications of chronic exposure to heavy materials are highlighted by the findings, which emphasizes the importance of monitoring and mitigation of environmental sources.